Franklin : the Autobiography and other writings on politics, economics, and virtue - Franklin, Benjamin, 1706-1790 (Cambridge texts in the history of political thought., 2004)
Alan Houston seeks to bring clarity to our understanding of Benjamin Franklin's political thought by making available, for the first time, a full and representative selection of his most important political writings. The entire text of the Autobiography is included alongside letters, essays, pamphlets, and manuscript notes.